Effects on Mood and EEG States After Meditation in Augmented Reality With and Without Adjunctive Neurofeedback - Viczko, Jeremy; Tarrant, Jeff; Jackson, Ray (Frontiers in Virtual Reality, 2021)
Research and design of virtual reality technologies with mental health focused application has increased dramatically in recent years. However, the applications and psychological outcomes of Augmented Reality (AR) technologies are remain to be as widely explored and evaluated. This is particularly true for the use of AR for self-management of stress, anxiety, and mood. In the current study, we examined the impact of a brief Open Heart meditation AR experience on participants with moderate levels of anxiety and/or depression. Using a randomized between-group design subjects participated in the AR experience or the AR experience plus frontal Gamma asymmetry neurofeedback integrated into the experience. Self-reported mood state and resting-state EEG were recorded before and after the AR intervention for both groups. Participants also reported on engagement and perceived use of the experience as a stress and coping tool. EEG activity was analyzed as a function of frontal, midline and parietal scalp regions, and with sLORETA current source density estimates of anterior cingulate and insular cortical regions of interest. Results demonstrated that both versions of the AR meditation significantly reduced negative mood and increased positive mood. The changes in resting state EEG were also comparable between groups, with some trending differences observed, in line with existing research on Open Heart and other loving-kindness and compassion-based meditations. Engagement was favorable for both versions of the AR experience, with higher levels of engagement reported with the addition of neurofeedback. These results provide early support for the therapeutic potential of AR integrated meditations as a tool for self-regulation of mood and emotion, and sets the stage for more research and development into health and wellness promoting AR applications.